Implementation of a Web-Based E-Library System for Optimizing Library Services: A Case Study of SMAN 1 Abung Pekurun - Rissa Pebrian; Sigit Gunanto (Sean Institute, 2025)
The library management system at SMAN 1 Abung Pekurun remains conventional, leading to several challenges such as inefficiency in book searching, vulnerability to data entry errors, and limited accessibility of information. This study aims to design and develop a web-based digital library system (E-Library) to address these problems. The system development method applied follows the Software Development Life Cycle (SDLC) using the Waterfall model, which includes the stages of requirement analysis, system design using Unified Modeling Language (UML), implementation with PHP and MySQL, and functional testing. The results demonstrate that the developed E-Library system is fully functional, having successfully passed 100% of 25 Black Box Testing scenarios. The system implementation effectively transformed the library’s manual operations into a digital platform, significantly improving service time efficiency, data accuracy, and information accessibility for users, while simplifying reporting processes for library staff and school management.